IMPLEMENTATION OF CASE BASED LEARNING TO IMPROVE STUDENTS' HIGHER ORDER THINKING SKILLS (HOTS) AT SMAN 1 BATIPUH - Kuntum Khaira Ummah; Nofrion (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low student motivation in learning, lack of student learning outcomes, minimal student understanding of HOTS questions, and lack of student participation in learning. Teachers still use inadequate and monotonous learning models, such as implementing lecture-based learning models that make students feel bored, making the learning less effective and enjoyable. The study aimed to determine how much influence the application of case-based learning to improve students' higher-order thinking skills (HOTS) at SMAN 1 Batipuh. The quantitative research method is experimental. This research design uses a pre-test-post-test control group design. The study population was 143 class XI geography students at Phase F of SMAN 1 Batipuh 2024/2025. The sampling technique was purposive sampling. The sample in this study selected two classes, of which 1 class was used as an experimental class, namely XI geo four and XI geo two as the control group. Data collection techniques were observation, documentation, and testing. The research instrument is a test sheet in the form of an objectif (case study) with an assessment according to the criteria of the higher-order thinking skills (HOTS) category, such as analyzing, evaluating, creating, thinking critically, and solving problems. The data analysis technique uses statistical analysis to process the data obtained. The data obtained from this study were processed with the help of IBM SPSS 30 for the T and N-gain tests. The study results revealed that the application of case-based learning positively improves students' high-order thinking skills (HOTS) in geography subjects at SMAN 1 Batipuh, as seen from students' learning outcomes and learning activities. The results of this study are that there is an effect of the application of Case Based Learning on population dynamics problem material to improve Higher Order Thinking Skills (HOTS) of students in class XI Geo 4. The average post-test of the experimental class was 83.48 and the control class was 53.80. Data analysis using the Paired T-Test from the calculation data obtained a significance level (sig) of 0.001 because the significance is less than 0.05, so HO is rejected and Ha is accepted.